The morphology and growth characterizations of Gambierdiscus pacificus Chinain et Faust 1999 - The, Ho Van; Mai Anh, Nguyen Thi (Academia Journal of Biology, 2012)
The benthic dinoflagellate of Gambierdiscus pacificus belonging to Dinophyta was isolated from Sargassum sp. (Phaeophyceae, Heterokontophyta) at Con Dao island of Ba Ria - Vung Tau province (106o 36’ E, 8o40’ N). Stock algal culture were kept in culture chamber with temperature 26 ± 0,5oC, light intensity of 45 mmol photons.m-2.s-1, and light:dark cycle of 12/12. Cells of G. pacificus are round to ellipsoid in apical view. Cells range in size from 55 - 60 mm in width, 50 - 55 mm in dorsoventral and 40 - 45 mm in length. The thecal surface is perforated by numerous pores. The formula plate: Po, 3’, 7’’, 6C, 8S, 5’’’, 1p, 2’’’’. The epitheca of G. pacificus consists of eleven plates: 1’, 2’, 3’, 1’’, 2’’, 3’’, 4’’, 5’’, 6’’, 7’’ and Po. The apical pore plate (Po) has a fish-hook-shaped with 28 round pores. The Po plate ranges 6.4 mm long and 4.3 mm wide, with a length/width ratio: 1.48. The apical plates 1’ and 3’ are small compared with apical plate 2’. The 2’ plate is narrow and rectangular. The cingulum is deep and narrow. The sulcus has a small and deep opening. The hypotheca consists of eight plates: 1’’’, 2’’’, 3’’’, 4’’’, 5’’’, 1’’’’, 2’’’’ and 1p. The 1p plate is short, narrow and pentagonal. The size of the 1p plate is 28 mm long and 12 mm wide, with length/width ratio: 2.33. The G. pacificus was grown at four salinities: 20, 25, 30 and 35‰ for each of the experimental temperatures 20, 23, 26, 29 and 32oC in flask 500 ml with T medium. Growth rates were low at salinity of 20‰ in all experimental temperatures (20, 23, 26, 29 and 32oC), and low at temperature of 32oC in all experimental salinities. The growth rates were rather high at salinities 30 and 35‰ in temperatures of 23, 26 and 29oC. G. pacificus grew best at: 30 and 35‰ in temperatures of 29oC. Maximal division rates was 0.54 ± 0.36 per two days. The highest cell density after 35 days culture reached 3,090 ± 92 cells.ml-1 at 35‰ (29oC); 2,480 ± 14 cells.ml-1 at 30‰ (29oC).